High on Crime? Exploring the Effects of Marijuana Dispensary Laws on Crime in California Counties - Priscillia E Hunt; Rosalie Liccardo Pacula; Gabriel Weinberger (Institute of Labor Economics (IZA), 2018)
Regulated marijuana markets are more common today than outright prohibitions across the U.S. states. Advocates for policies that would legalize marijuana recreational markets frequently argue that such laws will eliminate crime associated with the black markets, which many argue is the only link between marijuana use and crime. Law enforcement, however, has consistently argued that marijuana medical dispensaries (regulated retail sale and a common method of medical marijuana distribution), create crime in neighborhoods with these store-fronts. This study offers new insight into the question by exploiting newly collected longitudinal data on local marijuana ordinances within California and thoroughly examining the extent to which counties that permit dispensaries experience changes in violent, property and marijuana use crimes using difference-in-difference methods. The results suggest no relationship between county laws that legally permit dispensaries and reported violent crime. We find a negative and significant relationship between dispensary allowances and property crime rates, although event studies indicate these effects may be a result of pre-existing trends. These results are consistent with some recent studies suggesting that dispensaries help reduce crime by reducing vacant buildings and putting more security in these areas. We also find a positive association between dispensary allowances and DUI arrests, suggesting marijuana use increases in conjunction with impaired driving in counties that adopt these ordinances, but these results are also not corroborated by an event study analysis.
Keywords: K14; K42; H75; 330; crime; marijuana markets; local ordinances